ANALISIS PENGARUH INVESTASI, NET EKSPOR DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Yahya Yakaria Pangestin; Aris Soelistyo; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
Broadly, this research aims to find out how free variables affect Investment, Net Exports and Government Spending on Indonesia's Economic Growth. The type of data used is annual data starting from 2000 to 2019. The methods used are Partial Adjustment Model (PAM), Hypothesis Test and Classic Assumption Test. The results of the classic assumption test show that the normality test in this study meets the assumption of normality, the auto correlation test in this study did not have auto correlation and the heteroscedasticity test in this study avoided heteroscedasticity. Investment Variable has a positive effect on Indonesia's economic growth, Net Export variables have an insignificant positive effect on Indonesia's economic growth and Government Expenditure has a positive and significant effect on Indonesia's economic growth. Simultaneously variable Investment, Net Export and Government Expenditure simultaneously affect Indonesia's economic growth with a probability value of 0.0000.